Antimicrobial activity of crude epicarp and seed extracts from mature avocado fruit (Persea americana) of three cultivars - Raymond Chia, T.; Dykes, Gary (Informa Healthcare, 2010)
The epicarp and seed of Persea Americana Mill. var. Hass (Lauraceae), Persea Americana Mill. var. Shepard, and Persea americana Mill. var Fuerte cultivars of mature avocados (n = 3) were ground separately and extracted with both absolute ethanol and distilled water. Extracts were analyzed for antimicrobial activity using the microtiter broth microdilution assay against four Gram-positive bacteria, six Gram-negative bacteria, and one yeast. Antimicrobial activity against two molds was determined by the hole plate method. The ethanol extracts showed antimicrobial activity (104.2-416.7 µg/mL) toward both Gram-positive and Gram-negative bacteria (except Escherichia coli), while inhibition of the water extracts was only observed for Listeria monocytogenes (93.8-375.0 µg/mL) and Staphylococcus epidermidis (354.2 µg/mL). The minimum concentration required to inhibit Zygosaccharomyces bailii was 500 µg/mL for the ethanol extracts, while no inhibition was observed for the water extracts. No inhibition by either ethanol or water extracts was observed against Penicillium spp. and Aspergillus flavus. © 2010 Informa UK Ltd.